2007
DOI: 10.1104/pp.107.096933
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Expression of the Major Allergens in Developing and Germinating Peanut Seed

Abstract: Peanut (Arachis hypogaea) seed proteins Ara h 1, Ara h 2, and Ara h 3 are considered to be the major peanut allergens. However, little is known about their temporal and spatial expression during seed development and upon germination and seedling growth. In this study, transcript levels of the three major peanut allergen genes, ara h 1, ara h 2, and ara h 3, and their corresponding proteins were found in all cultivars. Expression patterns were heterogeneous depending on the specific peanut allergen gene and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 50 publications
4
29
0
Order By: Relevance
“…Qu et al (2008) found prolamin and endospermspecific motifs in all but one rice glutelin gene promoter which controlled seed specific expression. Our results for reporter gene expression in peanut under the control of the Ara h 2 promoter largely conform with the results obtained by Kang et al (2007b) who showed that Ara h 2 polypeptides were abundant in mature seeds and diminished after germination during seedling growth. An unexpected result was the lack of reporter gene expression in embryo axes, although expression in cotyledons was strong.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Qu et al (2008) found prolamin and endospermspecific motifs in all but one rice glutelin gene promoter which controlled seed specific expression. Our results for reporter gene expression in peanut under the control of the Ara h 2 promoter largely conform with the results obtained by Kang et al (2007b) who showed that Ara h 2 polypeptides were abundant in mature seeds and diminished after germination during seedling growth. An unexpected result was the lack of reporter gene expression in embryo axes, although expression in cotyledons was strong.…”
Section: Discussionsupporting
confidence: 91%
“…An unexpected result was the lack of reporter gene expression in embryo axes, although expression in cotyledons was strong. Furthermore, we did not detect Ara h 2 transcripts in either 2-wk-or 8-wk-old leaf tissues even though reporter gene transcripts could be observed as faint RT-PCR products in the 2-wk-old samples, data which also are consistent with Kang et al (2007b) who could not detect Ara h 2 transcripts in leaves by Northern blot analysis. The present study also shows that a higher copy number of the transgene did not result in a difference in the steady state level of transcripts.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Many PR10 proteins are constitutively expressed in various development stages and in seeds, roots (Sikorski et al, 1999), flowers, and leaves (Sikorski et al, 1999). Conversely, in Arachis hypogaea, 3 genes of allergenine (ara h1, ara h2, and ara h3) are exclusively expressed during seed development (Kang et al, 2007), and 2 homologs of the major allergen in Dacus carrota were highly expressed in the initial stages of embryogenesis and cellular suspension (Sano et al, 2004). Therefore, considering that contig 13686 was expressed in silico in a non-constitutive form, in lower intensities, in the libraries of leaves, plantlets, hypocotyls, and roots (AR1, LP1, CL2, FR4, RT5, and RT8) and in higher intensities in the embryogenic callus and cellular suspension libraries (CB1, CS1, PA1, and RT8), this contig may be involved in coffee plant embryogenesis.…”
Section: Est-contig 13686mentioning
confidence: 99%